2012
DOI: 10.1186/1748-717x-7-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of clinical trials of cetuximab combined with radiotherapy for non-small cell lung cancer

Abstract: Treatment of non-small cell lung cancer (NSCLC) is challenging in many ways. One of the problems is disappointing local control rates in larger volume disease. Moreover, the likelihood of both nodal and distant spread increases with primary tumour (T-) stage. Many patients are elderly and have considerable comorbidity. Therefore, aggressive combined modality treatment might be contraindicated or poorly tolerated. In many cases with larger tumour volume, sufficiently high radiation doses can not be administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Recent therapeutic strategies target the epidermal growth factor receptor (EGFR), which is overexpressed in about 40–50% of GBMs ( 15 ). There is evidence in the literature for such anti-EGFR therapeutics to improve the efficacy of conventional radiotherapy ( 16 ). EGFR is a member of the cell-surface receptor family ErbB and functions as an oncogene.…”
Section: Clinical Aspects Of Potential Side Effects Of Heavy Charged mentioning
confidence: 99%
“…Recent therapeutic strategies target the epidermal growth factor receptor (EGFR), which is overexpressed in about 40–50% of GBMs ( 15 ). There is evidence in the literature for such anti-EGFR therapeutics to improve the efficacy of conventional radiotherapy ( 16 ). EGFR is a member of the cell-surface receptor family ErbB and functions as an oncogene.…”
Section: Clinical Aspects Of Potential Side Effects Of Heavy Charged mentioning
confidence: 99%
“…Several studies reported the cost-effectiveness of widely accepted breast cancer therapies and found favorable ICERs [10,15,20]. For instance, anthracycline-based adjuvant trastuzumab regimen for a 49-year-old women with early-stage HER2-positive breast cancer had an ICER of $39,892/QALY [10], adjuvant trastuzumab chemotherapy for women with HER2-positive breast cancer had an ICER of $26,417/QALY [15], and a more recent study by Hedden et al reported that the adjuvant trastuzumab chemotherapy for women with HER2-positive breast cancer has an ICER of $13,095/QALY [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment for the RT intensification hypothesis was terminated earlier due to futility but recruitment for cetuximab met its accrual endpoint and 465 patients wer available for analysis (42 (38). Median OS were 15.1 and 19.6 months respectively, which favorably compares to historical controls of similar populations treated with radiotherapy alone (43). If this approach resists the test of randomized trials, it may have some benefit in this difficult to treat population.…”
Section: Clinical Developement In Combination With Radiotherapy For Smentioning
confidence: 99%